Electrochemical single-particle measurements of electrode materials for Li-ion batteries: Possibilities, insights and implications for future development. (10th January 2020) - Heubner, C.; Langklotz, U.; Lämmel, C.; Schneider, M.; Michaelis, A.
Abstract: The development of high performance active storage materials is considered one of the most promising approaches to increase the energy and power density of secondary batteries. The assessment of novel or refined active materials is typically done using composite electrodes, consisting of an active material, binder, conductive additive mixture coated on a metallic current collector foil. The electrochemical properties of such composite electrodes are known to be affected by their design, microstructure and composition, hence not representing the intrinsic properties of the active material employed. To overcome these constraints, researchers developed single-particle measurements (SPMs) that allow stripping away any matrix effects and determining the intrinsic properties of the active material used. Herein, the research progress of SPMs for investigations of active materials for secondary batteries is reviewed. The different experimental approaches to realize SPMs are presented and advantages and disadvantages are discussed. Results obtained with SPMs and composite electrodes are compared, regarding typical battery performance metrics and the analysis of insertion kinetics. The insights gained from the SPMs are discussed with respect to the most expedient development trends of future secondary batteries.